The activity of of vitexicarpin and artemetin in inhibiting hyperpigmentation: an in silico study - Riswana, I Kadek Rizki; Anjani, Ni Luh Ari Krisma; Susanti, Ni Made Pitri; Laksmiani, Ni Made Linda (Pharmacy Reports, 2023)
Hyperpigmentation, characterized by increased skin darkening, is primarily attributed to augmented melanin production, often exacerbated by UV ray exposure. Inhibiting melanogenesis enzymes, such as tyrosinase, tyrosinase-related protein 1, and d-dopachrome tautomerase, is a recognized strategy for managing hyperpigmentation. Flavonoid compounds, namely vitexicarpin and artemetin, have emerged as potential antihyperpigmentation agents. This study explores the inhibitory capabilities of vitexicarpin and artemetin on melanogenesis enzymes through in silico molecular docking. The process involved optimization of test compounds using HyperChem 8, target protein preparation with Chimera 1.11, method validation, and docking employing AutoDockTools 1.5.6, which integrates Autodock4 and Autogrid4 programs. The validity of the molecular docking method was confirmed with an RMSD value of ≤3 Å. The findings demonstrate that vitexicarpin and artemetin exhibit higher affinity towards tyrosinase, tyrosinase-related protein 1, and d-dopachrome tautomerase than the native ligands. Interaction models between the compounds and target proteins include hydrogen bonds, Van der Waals forces, hydrophobic interactions, and electrostatic bonds, with the most visually identifiable hydrogen bonds. These results suggest that vitexicarpine and artemetin have promising potential as antihyperpigmentation agents by inhibiting melanogenesis enzymes, as evidenced by the molecular docking approach.